Load –Deflection Relationship for Clamped- Horizontally Restrained R.C. Polygonal Slabs - Hassan, Ali Flayeh (Sulaimani Journal for Engineering Sciences, 2017)
A theoretical model is presented in the analysis and prediction of the complete load-deflection behavior of fixed-horizontally restrained reinforced concrete polygonal slabs under uniform loading. The limiting cases of fixed reinforced concrete square and circular slabs are also deduced. The proposed model considers three stages, elastic, elasto-plastic and plastic. In the elastic and -elasto-plastic stages, the results of classical plate theory are used. The cracking of concrete and yielding of steel reinforcement are accounted for by suitably modifying flexural rigidity. Changes that occur in support conditions due to possible yielding are also considered. In the plastic stage a rigid plastic membrane analysis is presented. A method is proposed to predict the real ultimate load (including membrane action) and the deflection at the ultimate load.
Keywords: Circular slabs; polygonal slab; square slabs; flexural rigidity; membrane action; yield criterion; yield-line theory